Carboxylesterase gene amplifications associated with insecticide resistance in Aedes albopictus: Geographical distribution and evolutionary origin. - Linda Grigoraki; Dimitra Pipini; Pierrick Labbé; Alexandra Chaskopoulou; Mylene Weill; John Vontas (Public Library of Science (PLoS), 2017)
BACKGROUND:Aedes albopictus is one of the most invasive human disease vectors. Its control has been largely based on insecticides, such as the larvicide temephos. Temephos resistance has been associated with the up-regulation, through gene amplification, of two carboxylesterase (CCE) genes closely linked on the genome, capable of sequestering and metabolizing temephos oxon, the activated form of temephos. PRINCIPAL FINDINGS:Here, we investigated the occurrence, geographical distribution and origin of the CCE amplicon in Ae. albopictus populations from several geographical regions worldwide. The haplotypic diversity at the CCEae3a locus revealed high polymorphism, while phylogenetic analysis showed an absence of correlation between haplotype similarity and geographic origin. Two types of esterase amplifications were found, in two locations only (Athens and Florida): one, previously described, results in the amplification of both CCEae3a and CCEae6a; the second is being described for the first time and results in the amplification of CCEae3a only. The two amplification events are independent, as confirmed by sequence analysis. All individuals from Athens and Florida carrying the CCEae3a-CCEae6a co-amplicon share a common haplotype, indicating a single amplification event, which spread between the two countries. SIGNIFICANCE:The importance of passive transportation of disease vectors, including individuals carrying resistance mechanisms, is discussed in the light of efficient and sustainable vector control strategies.